Treacher collins syndrome - Report of a classical case - Shweta Gangotri Sumbh; Jaishree Pagare; Bharat Sumbh (Wolters Kluwer Medknow Publications, 2017)
Treacher Collins syndrome (TCS) or Franceschetti syndrome is an autosomal dominant disorder of craniofacial development with variable expressivity. Incidence of this syndrome is approximately 1 in 50,000 live births and it affects both genders equally. This article describes clinical features of TCS in a 12-year-old female who had reported to the Department of Oral Medicine and Radiology. TCS affects structures which are derivatives of the first and second brachial arches which was also observed in this patient presenting with antimongoloid slanting of the palpebral fissures, colobomas of the lower eyelid, hypoplasia of zygoma and mandible, and an ear abnormality.